Reinventing the Criminalization of Commercial Sex Workers and Prostitution Service Users in Indonesia in the Perspective of Indonesian Criminal Law Reform - Ahmad Jamaludin (Universitas Ekasakti, 2024)
The advent of technology and easier internet access has led to a surge in internet and social media users in Indonesia, with apps like MiChat facilitating social interactions that could heighten the risk of HIV spread due to online prostitution. Commercial sex workers, once predominantly victims of trafficking, are increasingly promoting their services independently without intermediaries. This study aims to examine the enforcement of laws against online prostitution practices. The research method employed is normative juridical with a conceptual approach and statutory approach. The study finds that legal analysis of the criminalization of commercial sex work in Indonesia highlights the need for legislative renewal that emphasizes social justice and avoids disproportionate social consequences due to excessive criminalization. The necessary criminal law reform should harmonize sanctions with efforts for prevention, rehabilitation, and social reintegration to create a legal framework that supports individual well-being while maintaining social and moral integrity